Factors associated with lifetime suicide attempts: findings from the bipolar disorder course and outcome study from India (BiD-CoIN study). (3rd April 2023) - Grover, Sandeep; Avasthi, Ajit; Chakravarty, Rahul; Dan, Amitava; Chakraborty, Kaustav; Neogi, Rajarshi; Desouza, Avinash; Nayak, Omkar; Praharaj, Samir Kumar; Menon, Vikas; Deep, Raman; Bathla, Manish; et al.
Abstract: Aim: To evaluate the risk factors associated with lifetime suicide attempts in bipolar disorder (BD) patients. Methodology: 773 BD patients with a duration of illness of at least ten years, currently in clinical remission, were evaluated for suicidal attempts in their lifetime. Those with and without lifetime suicide attempt(s) were compared for various demographic and clinical risk factors. Results: 242 (31.3%) patients had a history of at least one lifetime suicide attempt. Compared to those without lifetime suicide attempts, those with suicidal attempts were less educated, were more often females, spent more time in episodes, and had a significantly more number of total episodes (in the lifetime, first five years of illness, and per year of illness), had significantly more number of total depressive episodes (in the lifetime, first five years of illness, and per year of illness), spent more time in depressive episodes, had more severe depressive episodes, more often had depression as the first episode in the lifetime, spent more time in mania/hypomania/mixed episodes, had higher residual depressive and manic symptoms, more often had rapid cycling affective disorder pattern in the lifetime, use of cannabis in dependence pattern, had poorer insight into their illness and had a higher level of disability (especially in three out of the four domains of Indian disability evaluation assessment scale). Conclusions: About one-third of the patients with BD have at least one-lifetime suicidal attempt, and those with suicide attempts usually have a poorer course of illness.